2018
DOI: 10.1111/arcm.12437
|View full text |Cite
|
Sign up to set email alerts
|

Is It Hop? Identifying Hop Fibres in a European Historical Context

Abstract: Hop (Humulus lupulus L.) is an ancient perennial crop plant, native to the Northern Hemisphere. The archaeological evidence dates back to at least the sixth century AD in Europe. Hop has been used for beer brewing, in sleeping draughts, as bedding and for antibacterial purposes. Less known is that hop fibres have also been used for textiles and paper. However, it is difficult to distinguish hop from other bast fibres. Here, we present a set of fibre features, which, when found together in an archaeological/his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In addition, microchemical tests using cuoxam-tetraamminediaquacopper dihydroxide [Cu(NH 3 ) 4 (H 2 O) 2 ](OH) 2 were performed at the end of investigation, in order to investigate the swelling behaviour (Luniak 1953, 80;Wülfert 1999, 281-282, 320;Stratmann 1973, 58-62). The investigations were performed following the recently developed identification method for hop fibres (Lukešová et al 2019). See also Fig.…”
Section: Methods Including Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, microchemical tests using cuoxam-tetraamminediaquacopper dihydroxide [Cu(NH 3 ) 4 (H 2 O) 2 ](OH) 2 were performed at the end of investigation, in order to investigate the swelling behaviour (Luniak 1953, 80;Wülfert 1999, 281-282, 320;Stratmann 1973, 58-62). The investigations were performed following the recently developed identification method for hop fibres (Lukešová et al 2019). See also Fig.…”
Section: Methods Including Sample Preparationmentioning
confidence: 99%
“…In this article, we present the first investigation on cultural heritage objects performed with the specific aim of finding out if they are made of hop; we use a very recently developed identification method (Lukešová et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper demonstrated that reliable identification of the unusual textile fibre hop can be achieved with a combination of several of the techniques listed above (Lukešová et al . 2019). An earlier publication shows how nettle can, in some cases, be distinguished from hemp and flax using polarisation microscopy (Bergfjord and Holst 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fibre cell characterization commonly uses light microscopy, which allows observations of internal and external morphological features such as overall dimensions (length, width), shape (e.g., round, flat, twisted), fibre end shape (e.g., pointed, forked, rounded), surface features (e.g., pitting, cross‐markings, dislocations) and wall irregularities (e.g., unevenness, scalloping) (Preston 1974; Ilvessalo‐Pfäffli 1995; Petraco and Kubic 2003b; Lukešová et al . 2019). However, reliance on morphological data alone can result in inaccurate identification because of non‐unique characteristics as well as high inter‐individual variation (e.g., Carr et al .…”
Section: Introductionmentioning
confidence: 99%
“…2017; Lukešová et al . 2019), including highlighting the anisotropic and birefringent (doubly diffracting) behaviour of materials such as fibre cells and crystal inclusions (Prychid and Rudall 1999; Petraco and Kubic 2003b). Fibre cell birefringence is due to helical polycrystalline layers within the fibre cell wall (Meylan and Butterfield 1978a; Bergfjord and Holst 2010; Haugan and Holst 2013), giving rise to diagnostic optical characteristics when viewed with cross‐polarized light (CPL) and a rotating stage.…”
Section: Introductionmentioning
confidence: 99%